Clinicopathological report of children and young adults with nephrotic syndrome undergoing renal biopsy at workshops in Port Harcourt, Nigeria - Obiorah, Christopher Chinedu; Okoro, Philemon Ekemenye (African Journal of Nephrology, 2018)
Background: Kidney biopsy is a procedure that is not commonly performed in Nigeria. This study reports the clinical and pathological findings in children who underwent renal biopsies during nephrology workshops held in Port Harcourt in 2014 and 2015. Methods: The native kidney biopsies were processed and evaluated with light microscopy only. Results: Nineteen patients (10 females) were biopsied. The mean age was 11.0 ± 6.5 years and the range was 1.8 to 21 years. Eleven patients had steroid-dependent nephrotic syndrome (SDNS) while eight were steroid-resistant (SRNS). Hypertension and haematuria were present more often in SDNS. There were 11 cases (57.9%) with non-proliferative lesions, including minimal change disease (4 cases), focal segmental glomerulosclerosis (4 cases) and collapsing glomerulopathy (3 cases). The proliferative lesions (8 cases) included membranoproliferative (mesangiocapillary) glomerulonephritis (MPGN, 5 cases), mesangial proliferative glomerulonephritis (2 cases) and MPGN with collapsing glomerulopathy (1 case). Overall, the most common pathologic diagnosis was MPGN (26.3%). Hypertension was more common with proliferative than non-proliferative lesions (62.5% versus 36.4%). Conclusions: Although MPGN was the most common morphologic lesion among children with nephrotic syndrome, bigger studies are necessary to confirm this. Efforts should be intensified in acquiring the expertise and infrastructure for performing and interpreting renal biopsies in Port Harcourt order to optimize patient management.